Biodiesel production from palm fatty acid distillate with carbon-based solid acid catalyst: A case study - Chia, Xing Zhe (2021)
Palm Fatty Acid Distillate (PFAD) is a by-product from palm oil refining industry. A considerable amount of PFAD is produced each year in Malaysia, and using it for biodiesel production is one of the methods to utilize it. The suitability of PFAD in biodiesel production was studied through esterification reaction catalysed by the carbon-based solid acid catalyst. Various esterification parameters such as reaction temperature (30 °C – 70 °C), reaction time (30 min – 110 min), alcohol to oil molar ratio (3 : 1 – 11 : 1) and catalyst loading (1.0 wt% - 3.0 wt%) were studied with PFAD as feedstock. The study was simulated through response surface methodology (RSM) with central composite design (CCD) by using Design Expert 10 Simulation Software. Their individual and interactions effects on biodiesel yield were discussed and compared. From the simulation, reaction time and interaction between reaction time and catalyst concentration showed the highest influence on biodiesel yield. While comparing with other journals, the degree of influence for each parameter on biodiesel yield is mainly dependent on the setup of the experiment. On the other hand, the effects of different sulfonation methods on biodiesel yield had been discussed and catalyst that produced through arylation of diazonium salt had a better performance compared to direct sulfonation. Lastly, various catalyst synthesis parameters such as sulfonation temperature (100 °C – 500 °C), sulfonation time (1 h – 9 h), weight of catalyst support (1 g – 5 g) and volume of acid used for sulfonation (100 ml – 500 ml) on biodiesel yield was simulated with RSM-CCD. Their individual and interactions effects on biodiesel yield were discussed and compared. From the simulation, the volume of acid used for sulfonation and the interaction between weight of catalyst support and volume of acid used for sulfonation showed the highest influence on biodiesel yield. This project is able to provide some data such as suitable esterification parameters and sulfonation parameters for future experiment and optimization. Besides that, researchers are able to know which sulfonation method to be use for future experiment setup. Lastly, information on the characterization of solid acid catalyst was also provided in this study.